2008
DOI: 10.1161/circulationaha.107.695254
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Localization of High-Risk Coronary Atherosclerotic Plaques on the Basis of Low Endothelial Shear Stress

Abstract: Background-Low endothelial shear stress (ESS) promotes the development of atherosclerosis; however, its role in the progression of atherosclerotic plaques and evolution to inflamed high-risk plaques has not been studied. Our hypothesis was that the lowest values of ESS are responsible for the development of high-risk coronary atherosclerotic plaques associated with excessive expansive remodeling. Methods and Results-Twenty-four swine, treated with streptozotocin to induce diabetes and fed a high-fat diet, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
298
0
34

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 363 publications
(355 citation statements)
references
References 24 publications
23
298
0
34
Order By: Relevance
“…There are few reports on the modulation of lipid homeostasis by diet in pigs despite the fact that pigs and minipigs are widely used as animal models for important human pathologies such as atherosclerosis. A hypercholesterolemic diet is a validated model for inducing experimental atherosclerosis (Dixon et al, 1999;Geeraert et al, 2007;Chatzizisis et al, 2008). Pigs can develop hypercholesterolemia and atherosclerotic lesions after the administration of high-cholesterol diets, reaching plasma cholesterol levels similar to those in humans.…”
Section: Introductionmentioning
confidence: 99%
“…There are few reports on the modulation of lipid homeostasis by diet in pigs despite the fact that pigs and minipigs are widely used as animal models for important human pathologies such as atherosclerosis. A hypercholesterolemic diet is a validated model for inducing experimental atherosclerosis (Dixon et al, 1999;Geeraert et al, 2007;Chatzizisis et al, 2008). Pigs can develop hypercholesterolemia and atherosclerotic lesions after the administration of high-cholesterol diets, reaching plasma cholesterol levels similar to those in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports stressed the importance of WSS and OSI with respect to the formation and stability of atherosclerotic plaques (4). A number of studies have shown that low WSS and high OSI represent sensitive markers for formation of plaques in the aorta, carotid, or coronary arteries (5,6). Particularly, the assessment of both WSS and OSI can help to determine the complexity of the lesions.…”
mentioning
confidence: 99%
“…These areas tend to occur at the outer walls of arterial branch points and have been shown to induce endothelial dysfunction [3].…”
Section: Introductionmentioning
confidence: 99%